2006
DOI: 10.1079/phn2005925
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive and any breast-feeding rates of Pacific infants in Auckland: data from the Pacific Islands Families First Two Years of Life study

Abstract: Objectives: To present current breast-feeding rates for Pacific infants resident in New Zealand. Reasons for the introduction of complementary liquid foods were also explored. Design: A longitudinal study using hospital discharge summary records and maternal home interviews undertaken at 6 weeks, 12 and 24 months postpartum. Turnbull's non-parametric survival analysis was used to model exclusive breast-feeding rates. Setting: Auckland, New Zealand. Results: The cohort comprised 1376 infants at 6 weeks, 1223 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…In our study of Pacific infants with median age of 7 weeks, 50% were fully breastfed. The difference between the Ministry’s and our figures is likely primarily due to the age‐dependent decline in breastfeeding rates 31 . Although undoubtedly conferring substantial benefits to both mother and child, 32 not all studies support breastfeeding as a protective factor for SIDS 33 .…”
Section: Discussionmentioning
confidence: 62%
“…In our study of Pacific infants with median age of 7 weeks, 50% were fully breastfed. The difference between the Ministry’s and our figures is likely primarily due to the age‐dependent decline in breastfeeding rates 31 . Although undoubtedly conferring substantial benefits to both mother and child, 32 not all studies support breastfeeding as a protective factor for SIDS 33 .…”
Section: Discussionmentioning
confidence: 62%
“…This suggestion was not intended to undermine breastfeeding but rather to promote further research into this important issue. Mothers themselves commonly cite concern that their breast milk has become insufficient as a source of nutrition for their infant as a reason for introducing formula-milk or complementary foods (39,40); hence, evidence on the breast-milk intakes of EBF infants will help encourage mothers to breastfeed. In the present study, we have shown that the large majority (77%) of a sample of mothers practicing EBF at 4 mo successfully continued EBF to 6 mo, with their infants showing adequate growth.…”
Section: Discussionmentioning
confidence: 99%
“…34 Additionally, Schluter, Carter, and Percival conducted a study of Pacific Islanders in New Zealand and found that a growing concern to breastfeeding duration is the uncertainty of breast milk supply. 35 Research indicates that perceived insufficient milk supply is commonly due to mothers’ lack of education and understanding of effective techniques to increase milk supply. 35 Concurrently, Abdulraheem and Binns found that, among Maldivian mothers, the main reason given for mothers ceasing breastfeeding was the introduction of formula due to beliefs of low milk supply.…”
Section: Introductionmentioning
confidence: 99%